7(x+2)=5x+2+6x

Simple and best practice solution for 7(x+2)=5x+2+6x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 7(x+2)=5x+2+6x equation:


Simplifying
7(x + 2) = 5x + 2 + 6x

Reorder the terms:
7(2 + x) = 5x + 2 + 6x
(2 * 7 + x * 7) = 5x + 2 + 6x
(14 + 7x) = 5x + 2 + 6x

Reorder the terms:
14 + 7x = 2 + 5x + 6x

Combine like terms: 5x + 6x = 11x
14 + 7x = 2 + 11x

Solving
14 + 7x = 2 + 11x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-11x' to each side of the equation.
14 + 7x + -11x = 2 + 11x + -11x

Combine like terms: 7x + -11x = -4x
14 + -4x = 2 + 11x + -11x

Combine like terms: 11x + -11x = 0
14 + -4x = 2 + 0
14 + -4x = 2

Add '-14' to each side of the equation.
14 + -14 + -4x = 2 + -14

Combine like terms: 14 + -14 = 0
0 + -4x = 2 + -14
-4x = 2 + -14

Combine like terms: 2 + -14 = -12
-4x = -12

Divide each side by '-4'.
x = 3

Simplifying
x = 3

See similar equations:

| 3x^3-10x^2+50x= | | -2a-9= | | 8(r-2)=r-22+5r | | x*x+x-1=0 | | 9x-4x+3=60 | | x^2+26x+64=0 | | K-14+5k=2(k+3) | | 6y=5x^2-2 | | x-2=x*x-1 | | K-18+5k=2(k+1) | | 2(9x-6)+8(6x-7)=-29 | | 19+6y-1=17y-9-2y | | -32-19y+19=-29y+31+6y | | 11k+2=k+18 | | (4x-3)(x+7)=(1-2x)(x-9) | | x^2-32x+256-37=0 | | -31-3y+18=-22y+3+15y | | -3c+5+5c=-3c+20 | | (2x+1)(x-16)=(3x-2)(x-6) | | 2t-1=3(t+3) | | Y=2x(7x-3) | | 9(3+2x)=10x+45 | | 8(y-2)=4y-28 | | 2-6x+10x=-2(-3x+4) | | 25+3y-6=13y-11-4y | | x^2-32x+256=37 | | 21+3y-2=13y-11-4y | | 2*3*2*11+9/3= | | 16-4x=3x+2 | | 7y-7=4y+2 | | (x-16)(x-16)= | | 8-3x=-6+4x |

Equations solver categories